Developmental dynamics and functional adaptation of gut microbiota in Mongolian wild asses (Equus hemionus hemionus) across ontogenetic stages in arid desert ecosystems - Wang, Jianeng; Gu, Haifeng; Gao, Hongmei; Zhang, Tongzuo; Li, Bin; Zhang, Meng; Jiang, Feng; Song, Pengfei; Liang, Chengbo; Fan, Qing; Xu, Youjie; Zhang, Ruidong (Frontiers in Microbiology, 2025)
Understanding the composition and function of gut microbiota is essential for elucidating how wild animals adapt to arid environments. The Mongolian wild ass (Equus hemionus hemionus), which inhabits harsh desert ecosystems, offers an ideal model for such investigations. This study employed metagenomic sequencing of fecal samples to characterize the composition and structure of the gut microbiota in adult, subadult, and juvenile Mongolian wild asses, with functional annotation based on the KEGG, CARD, and CAZy databases. Our study revealed that Bacillota and Bacteroidota were the dominant phyla, together accounting for over 85% of relative abundance, with their ratio (B/B value) showing clear age-dependent shifts. Juveniles were dominated by Bacillota (high B/B value), consistent with adaptation to a milk-based, protein- and lactose-rich diet, whereas adults shifted toward Bacteroidota dominance (low B/B value), with relative abundance increasing from 39.53% to 64.92%, reflecting enhanced polysaccharide and fiber degradation, thereby providing microecological support for adaptation to low-energy, high-fiber desert vegetation resources. Alongside this transition, α-diversity significantly increased with age, while β-diversity patterns shifted from dispersed to clustered, indicating a more complex, stable, and mature gut community. Over 58% of predicted genes were assigned to metabolic pathways, highlighting the essential contribution of gut microbes to herbivore digestion. Polysaccharide lyases, enriched in adults and subadults, were positively correlated with Bacteroidota abundance, highlighting their central role in fiber degradation and stable energy supply, thereby supporting adaptation to arid desert habitats. In contrast, juveniles were characterized by enrichment of the galactose metabolism pathway, high abundance of Pseudomonadota (LEfSe LDA > 4), and the largest number of antibiotic resistance genes (AROs), including 17 potential key AROs, reflecting greater microbial plasticity and higher environmental exposure risks during early development. This study provides the first systematic characterization of age-related gut microbiome dynamics and functional adaptations in the endangered Mongolian wild ass, offering novel insights into microbial contributions to host energy optimization and resilience in arid ecosystems, with implications for conservation strategies.